2021
DOI: 10.3390/ijerph18178908
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Department of Housing and Urban Development’s Smoke-Free Rule: A Socio-Ecological Qualitative Assessment of Administrator and Resident Perceptions

Abstract: In July 2018, the United States Department of Housing and Urban Development (HUD) implemented a mandatory smoke-free rule in public housing. This study assessed administrator and resident perceptions of rule implementation during its initial year in the District of Columbia Housing Authority (DCHA). Assessment included nine focus groups (n = 69) with residents and in-depth interviews with administrators (n = 7) and residents (n = 26) from 14 DCHA communities (family = 7 and senior/disabled = 7). Semi-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Results from other investigations indicate DCHA reported that they offered general smoking cessation classes and quitline resources to residents who wanted to quit, but the classes were poorly attended, and many residents reported not knowing about those resources. ( Horn et al, 2021;18(17):8908. )…”
Section: Discussionmentioning
confidence: 99%
“…Results from other investigations indicate DCHA reported that they offered general smoking cessation classes and quitline resources to residents who wanted to quit, but the classes were poorly attended, and many residents reported not knowing about those resources. ( Horn et al, 2021;18(17):8908. )…”
Section: Discussionmentioning
confidence: 99%
“…Results indicating few ever e-cigarette users are current users and most residents use e-cigarettes fewer than 10 times in their lives suggest residents use e-cigarette products a few times but do not adopt their use as a consistent behavior. Low interest and uptake among residents may be due to high cost and low availability of e-cigarettes ( Cheng et al, 2021 ), and the sample primarily consisting of respondents with lower levels of knowledge, access, and use of e-cigarettes ( Horn et al, 2021a , Horn et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in use may adversely impact the health of residents as e-cigarettes are harmful to users and may carry unique health risks despite being less harmful than combustible cigarettes ( US Department of Health and Human Services, 2020 , National Academies of Sciences, Engineering, and Medicine et al, 2018 ), and secondhand e-cigarette aerosol exposure can impact the health of other residents ( Visser et al, 2019 ). If this is the case, the update to the rule should involve a community input to improve low levels of trust associated with implementing the rule to date ( Horn et al, 2021b , Wray et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flyers for the study were placed in common areas in buildings notifying residents where and when data collection events would be held, and resident council presidents and DCHA staff told residents about data collection events during community meetings. During data collection events, residents frequently found out about the event from other residents (word-of-mouth) 23 24. Interested residents completed a screening assessment to establish residence and age eligibility and past 30-day smoking status.…”
Section: Methodsmentioning
confidence: 99%